A comparative study of National Family Health Survey-4 and National Family Health Survey-5 on nutritional indicators in Assam - Saeed, Aamir; Sharma, Sthapana; Habib, Ashfia; Ojah, Jutika (International Journal Of Community Medicine And Public Health, 2025)
When evaluating the health and wellbeing of children, nutritional indicators are essential. The National Family Health Surveys (NFHS) in India offer thorough data on these metrics. The nutritional status of Assamese children under five from NFHS-4 (2015–16) and NFHS-5 (2019–21) is examined in this study. This comparative study aimed at understanding the changes in indicators of nutrition, such as stunting, wasting, and prevalence of underweight among children aged below five years in Assam through data comparison in NFHS-4 and NFHS-5. Regional differences and trends in access to healthcare were explored in the study. The study discovered a range of nutritional consequences. Stunting decreased little from 36.4% to 35.3%, whereas wasting increased sharply from 17% to 21.7%. Additionally, the prevalence of underweight rose from 29.8% to 32.8%. There were still regional disparities, with the Barak Valley showing concerningly high levels of hunger. Nutritional outcomes have remained unchanged or worsened in spite of improvements in mortality rates and access to healthcare. The results highlight the significance of focused efforts on Assamese regional disparities, sanitation, and food security. Increasing acute malnutrition necessitates policy adjustments targeted at high-burden areas, notwithstanding improvements in healthcare access and mortality declines.